2020
DOI: 10.22541/au.159414621.12510552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early recovery patterns of olfactory disorders in COVID-19 patients; A clinical cohort study

Abstract: Introduction: A rapidly evolving evidence suggests that smell dysfunction is a common symptom in COVID-19 infection with paucity of data on its duration and recovery rate. Objectives: delineate the different patterns of olfactory disorders recovery in patients with COVID-19. Methods: This cross-sectional cohort study included 96 patients with olfactory complaint confirmed to be COVID-19 positive with recent onset of anosmia. All patients were inquired for smell recovery patterns using self-assessment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…The results of the current study suggest that smoking can adversely affect the recovery time of anosmia ( Table 2 ). Similar effect can be extrapolated from the study of Amer et al [ 42 ] who reported that significant proportion of smoking patients was not recovered within one month from the onset of COVID-19-associated olfactory dysfunction. This could be attributed to the negative impact of smoking on the regeneration of olfactory epithelium as previously demonstrated in mice [ 43 ].…”
Section: Discussionsupporting
confidence: 71%
“…The results of the current study suggest that smoking can adversely affect the recovery time of anosmia ( Table 2 ). Similar effect can be extrapolated from the study of Amer et al [ 42 ] who reported that significant proportion of smoking patients was not recovered within one month from the onset of COVID-19-associated olfactory dysfunction. This could be attributed to the negative impact of smoking on the regeneration of olfactory epithelium as previously demonstrated in mice [ 43 ].…”
Section: Discussionsupporting
confidence: 71%
“…Our study showed that the mean age of patients was 39. (26); but in the study of Meini et al, that conducted on hospitalized patients, the mean age was 65 ± 15 years, this difference may to be due to the difference in the studied population (25).…”
Section: Discussionmentioning
confidence: 84%
“…Hopkins et al, reported a 79% recovery rate over the course of a month (30). Amer et al, reported complete and partialOD recovery rate of 96 patients with COVID-19; this rate was 33% and 41% for complete and partial recovery respectively within 11 days, while 25% did not achieve any recovery during one month(26). In a study by Vaira et al, 7.3% of patients still had severe disorders during the two-month follow-up (31).…”
mentioning
confidence: 99%
“…Other studies have shown almost the same ndings as our study, including the study of Gorzkowski et al that reported a mean age of 39.7 ± 13.7 years (23) and the study of Romero-Gameros et al that reported a mean age of patients of 41 ± 13 years (21). In the study of Lechien et al, the mean age of patients was 36.9 ± 11.4 years (24) and in the study of Amer et al the mean age of patients was 34.26 ±11.91 years (26); but in the study of Meini et al, that conducted on hospitalized patients, the mean age was 65 ± 15 years, this difference may to be due to the difference in the studied population (25).…”
Section: Discussionmentioning
confidence: 94%
“…Hopkins et al, reported a 79% recovery rate over the course of a month (30). Amer et al, reported complete and partial OD recovery rate of 96 patients with COVID-19; this rate was 33% and 41% for complete and partial recovery respectively within 11 days, while 25% did not achieve any recovery during one month (26). In a study by Vaira et al, 7.3% of patients still had severe disorders during the two-month follow-up (31).…”
Section: Discussionmentioning
confidence: 98%